Platelet-derived- Extracellular Vesicles Promote Hemostasis and Prevent the Development of Hemorrhagic Shock - Lopez, Ernesto; Srivastava, Amit K.; Burchfield, John; Wang, Yao-Wei; Cardenas, Jessica C.; Togarrati, Padma Priya; Miyazawa, Byron; Gonzalez, Erika; Holcomb, John B.; Pati, Shibani; Wade, Charles E. (Scientific reports, 2019)
Every year more than 500,000 deaths are attributed to trauma worldwide and severe hemorrhage is present in most of them. Transfused platelets have been shown to improve survival in trauma patients, although its mechanism is only partially known. Platelet derived-extracellular vesicles (PEVs) are small vesicles released from platelets upon activation and/or mechanical stimulation and many of the benefits attributed to platelets could be mediated through PEVs. Based on the available literature, we hypothesized that transfusion of human PEVs would promote hemostasis, reduce blood loss and attenuate the progression to hemorrhagic shock following severe trauma. In this study, platelet units from four different donors were centrifuged to separate platelets and PEVs. The pellets were washed to obtain plasma-free platelets to use in the rodent model. The supernatant was subjected to tangential flow filtration for isolation and purification of PEVs. PEVs were assessed by total count and particle size distribution by Nanoparticle Tracking Analysis (NTA) and characterized for cells of origin and expression of EV specific-surface and cytosolic markers by flow cytometry. The coagulation profile from PEVs was assessed by calibrated automated thrombography (CAT) and thromboelastography (TEG). A rat model of uncontrolled hemorrhage was used to compare the therapeutic effects of 8.7 × 10 8 fresh platelets (FPLT group, n = 8), 7.8 × 10 9 PEVs (PEV group, n = 8) or Vehicle (Control, n = 16) following severe trauma. The obtained pool of PEVs from 4 donors had a mean size of 101 ± 47 nm and expressed the platelet-specific surface marker CD41 and the EV specific markers CD9, CD61, CD63, CD81 and HSP90. All PEV isolates demonstrated a dose-dependent increase in the rate and amount of thrombin generated and overall clot strength. In vivo experiments demonstrated a 24% reduction in abdominal blood loss following liver trauma in the PEVs group when compared with the control group (9.9 ± 0.4 vs. 7.5 ± 0.5 mL, p < 0.001>). The PEV group also exhibited improved outcomes in blood pressure, lactate level, base excess and plasma protein concentration compared to the Control group. Fresh platelets failed to improve these endpoints when compared to Controls. Altogether, these results indicate that human PEVs provide pro-hemostatic support following uncontrolled bleeding. As an additional therapeutic effect, PEVs improve the outcome following severe trauma by maintaining hemodynamic stability and attenuating the development of ischemia, base deficit, and cardiovascular shock.